Análisis del modelo de negocio del club de futbol profesional Independiente del Valle - Chala Valverde, Pablo Alexis (2024)
Football, besides being the world's most popular sport, is a multi-billion dollar industry. Its confederations and federations participate in the million-dollar share of this pie. But it is the teams and the players who are the resource-generating companies that enable the juicy revenues. For this reason, it is necessary to discover and unveil the administrative and economic structure that football clubs and teams apply to achieve their financial goals. Today, this administrative procedure is known as the Business Model. However, beyond the business model, it is necessary to know how the football business became professionalised and for this we need to know its history. Knowing its history, we can determine the evolution of the Business Model over time, from as far back as the 19th century. Nowadays, the sports Business Model has become a necessity and it is necessary to analyse it and determine its structure, as well as to unveil those teams that have been pioneers in applying it in reality. Independiente del Valle has also applied its Business Model in Ecuador, which has been a resounding success in a few lustrums since Mr. Michel Deller took over the club. The main objective of this study is to determine the Know How of their success, as well as to determine their Business Model.